1987
DOI: 10.1037/h0079996
|View full text |Cite
|
Sign up to set email alerts
|

Public views of sentencing: The role of offender characteristics.

Abstract: The equitable allocation of punishment is a major purpose of any judicial system. Perceptions of equity depend in large degree on the correspondence between judicial practice and the attitudes of the community. Specifically, if sentencing judges employ mitigating factors that the public do not support, sentences will be perceived to be inequitable. For example, if judges assign more lenient sentences to employed compared to unemployed offenders, this will disturb members of the public unless they also believe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 13 publications
3
19
2
Order By: Relevance
“…This study, and most other research, failed to show that public demand led to more severe sentences. Rather, research showed that public opinion was not consistent with the passage of sentencing legislation (Cullen, Fisher, & Applegate, 2000;Gebotys & Roberts, 1987;Tonry, 1999). Cullen, Clark, and Wozniak (1985, p. 16) are equally critical of the assumption that sentence practices reflect public attitudes.…”
Section: Discussionmentioning
confidence: 94%
“…This study, and most other research, failed to show that public demand led to more severe sentences. Rather, research showed that public opinion was not consistent with the passage of sentencing legislation (Cullen, Fisher, & Applegate, 2000;Gebotys & Roberts, 1987;Tonry, 1999). Cullen, Clark, and Wozniak (1985, p. 16) are equally critical of the assumption that sentence practices reflect public attitudes.…”
Section: Discussionmentioning
confidence: 94%
“…Most of the characteristics of offenders that have been included in models of perceptions of sentencing have had little effect on sentencing decisions (Gebotys & Roberts, 1987). The strongest effect comes from an offender's prior record, which people may view as an indicator of both the entrenchment of the offender in a criminal lifestyle (past behavior), and the potential for future criminal behavior (Zamble & Kahn, 1990).…”
Section: Perceptions Of Sentencingmentioning
confidence: 99%
“…In particular, sentencing may be guided by utilitarian rather than just-desert rationales (Gebotys & Roberts, 1987;Steffensmeier et al, 1998). Here, such goals as deterrence, incapacitation, and rehabilitation may determine how the offender is treated (Gebotys & Roberts;Kapardis & Farrington, 1981). A heavier sentence may be given to warn others what will happen to them if they commit the same crime, for deterrence, or to keep the criminal out of public circulation, for incapacitation.…”
mentioning
confidence: 99%
“…Actions like this, which Canadian case law has supported (Gebotys & Roberts, 1987), may be justifiable if they are based on empirically demonstrated risk factors for reoffending. In fact, investigators have related race and gender, which are thought to predict recidivism, to processing by the criminal justice system (Wilbanks, 1988) and to judgments that the system has made under experimental conditions (Mazzella & Feingold, 1994).…”
mentioning
confidence: 99%